Polyamide-imide copolymer as well as preparation method and application thereof

Through the copolymerization technology of polymerized monomers, the combination of dianhydride, diamine and diacyl chloride compounds is used to inhibit the formation of charge transfer complexes, improve the optical and mechanical properties of polyimide films, and solve its application in the field of photoelectricity Limitation, high-performance polyamide-imide copolymer films are achieved.

CN119119474APending Publication Date: 2024-12-13OLED (SHANGHAI) MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411134024.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Due to the particular molecular structure, the polyimide film has a conjugated aromatic structure and charge transfer complex, resulting in brown or yellow color, which limits its application in the field of photoelectricity, and its mechanical and optical properties are not sufficient to meet the high-tech field. demand.

Method used

The dianhydride compound, diamine compound and diacyl chloride compound in the polymerized monomer are used for copolymerization. By introducing cyclic aliphatic and aromatic monomers, the electron cloud density is reduced, the band gap difference of large molecule orbital energy level is reduced, and the charge transfer is inhibited. The formation of complexes improves optical properties and improves mechanical and optical properties by adjusting the molar ratio and reaction sequence.

Benefits of technology

The excellent mechanical and optical properties of the polyamide-imide copolymer film are achieved, the deterioration of the yellow index is avoided, the transparency and mechanical strength are improved, and it is suitable for the fields of optoelectronics and flexible sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004998822610000261
    Figure BDA0004998822610000261
  • Figure BDA0004998822610000271
    Figure BDA0004998822610000271
Patent Text Reader

Abstract

The invention provides a polyamide-imide copolymer as well as a preparation method and application thereof, the polyamide-imide copolymer is a copolymer obtained by polymerizing polymeric monomers, and the polymeric monomers comprise a dianhydride compound, a diamine compound and a diacyl chloride compound. The polyamide-imide copolymer provided by the invention can improve mechanical properties when forming a film, and can retain high optical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials and relates to a polyamide-imide copolymer and a preparation method and application thereof. Background Art

[0002] In view of the fragility of tempered glass in response to external impact, optical plastic films, especially those with excellent high and low temperature resistance, electrical insulation, excellent mechanical strength, chemical stability, aging resistance and radiation resistance, are gradually becoming a hot spot for research and application. In this field, high-performance plastic materials such as polyethylene terephthalate, polyethersulfone, polyethylene naphthalate, polyacrylate, polycarbonate, polyimide, polyaramid, etc., are expanding their application boundaries in high-tech fields with their unique advantages. Among them, polyimide resin, as an insoluble and infusible super heat-resistant resin, has a unique molecular structure design that gives it extraordinary heat oxidation resistance, heat resistance, radiation resistance, low temperature resistance, chemical resistance and other excellent properties. These excellent properties make polyimide play an irreplaceable role in the field of electronic materials, such as insulating coating materials, insulating films, semiconductors, electrode protective films, etc.

[0003] As display devices pay more and more attention to lightweight, thin and flexible, research on replacing glass with polyimide is actively carried out, and the performance requirements are constantly increasing. The resin composition of the related invention can give the film excellent mechanical and optical properties. Although polyimide has advantages such as thermal stability, mechanical properties and optical transparency, it has great application potential in many fields such as optoelectronics and flexible sensors. However, due to the particularity of the molecular structure of polyimide, there are conjugated aromatic structures and charge transfer complexes, which make it appear brown or yellow, limiting its application in the optoelectronic field. Summary of the invention

[0004] In view of the shortcomings of the prior art, the object of the present invention is to provide a polyamide-imide copolymer and a preparation method and application thereof. The polyamide-imide copolymer of the present invention can impart excellent mechanical properties to the film and has excellent optical properties.

[0005] To achieve this object, the present invention adopts the following technical solutions:

[0006] In one aspect, the present invention provides a polyamide-imide copolymer, wherein the polyamide-imide copolymer is a copolymer obtained by polymerizing monomers, wherein the polymerizing monomers include a dianhydride compound, a diamine compound, and a diacid chloride compound.

[0007] Preferably, the dianhydride compound is selected from any one or a combination of at least two of aliphatic or aromatic dianhydrides.

[0008] Preferably, the dianhydride compound is selected from 1,2,4,5-cyclohexanetetracarboxylic dianhydride (HPMDA), 2,3',3,4'-biphenyltetracarboxylic dianhydride (A-BPDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (S-BPDA), 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA), 1,2,3,4-cyclopentanetetracarboxylic dianhydride (CPDA), 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride (BPAF), 1,2,3,4-cyclohexanetetracarboxylic dianhydride (CHDA), 5-(2,5-dioxytetrahydrofuranyl)-3-methylcyclohexene-1,2-dicarboxylic dianhydride (DOCDA), 1,3-diethylcyclobutane-1,2,3,4-tetracarboxylic dianhydride (DE CBDA), 1,3-diphenylcyclobutane-1,2,3,4-tetracarboxylic dianhydride (DPhCBDA), 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic dianhydride (TDA) and their derivatives, or a combination of at least two thereof.

[0009] More preferably, the dianhydride compound is selected from any one or more combinations of 3,3',4,4'-biphenyltetracarboxylic dianhydride (S-BPDA), cyclobutanetetracarboxylic dianhydride (CBDA) and 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride (BPAF).

[0010] Preferably, the diamine compound can be selected from 2,2'-bis(trifluoromethyl)benzidine (TFMB), 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane (4BDAF), 2,2-bis(3-amino-4-hydroxyphenyl)-hexafluoropropane (6FAP), 3,4'-diaminodiphenyl ether (ODA), p-phenylenediamine (pPDA), m-phenylenediamine (mPDA), p-diaminodiphenylmethane (pMDA), m-diphenylamine (mMDA) , 1,3-bis(3-aminophenoxy)benzene (133APB), 1,3-bis(4-aminophenoxy)benzene (134APB), 1,4-bis(4-aminophenoxy)benzene (144APB), bis(4-aminophenyl)sulfone (4DDS), bis(3-aminophenyl)sulfone (3DDS), 2,2-bis[4-(4-aminophenoxy)phenyl]propane (6HMDA) and any one or a combination of at least two of their derivatives, and is not necessarily limited thereto.

[0011] More preferably, the diamine compound is 2,2'-bis(trifluoromethyl)benzidine (TFMB).

[0012] Preferably, the diacyl chloride compound is selected from any one or a combination of at least two of terephthaloyl chloride (TPC), isophthaloyl chloride (IPC), phthaloyl chloride, [1,1'-biphenyl]-4,4'-dicarboxylic acid chloride (BPC), 1,4-naphthalene dicarboxylic acid chloride (NPC), 2,6-naphthalene dicarboxylic acid chloride (NTC), 1,5-naphthalene dicarboxylic acid chloride (NEC), glutaryl chloride, adipoyl chloride and their derivatives, and is not necessarily limited thereto.

[0013] More specifically, the diacid chloride is preferably any one of terephthaloyl dichloride (TPC) and isophthaloyl dichloride (IPC) or a combination of both.

[0014] Normally, the charge transfer complex (CTC) within and between polyimide molecules will make the polyimide film appear yellow or brown, thus affecting the optical properties of the film. By introducing cyclic aliphatic and bulky aromatic monomers, the electron cloud density can be reduced, the molecular orbital energy level band gap difference between HOMO and LUMO can be widened, and the formation of CTC can be inhibited, thereby improving the optical properties. By adding aromatic structures with strong rigidity and diacyl chloride monomers, the mechanical properties can be improved and balanced.

[0015] In addition, although not limited by a particular theory, the raw material monomer contains an aromatic ring, which can increase the carbon content of the polyamide-imide resin and allow the resin to have a more rigid structure. Therefore, a film having excellent mechanical physical properties and sufficient optical physical properties can be provided.

[0016] Preferably, the molar ratio of the diamine compound to the diacyl chloride compound and the dianhydride compound is 1:0.1-0.9:0.9-0.1, preferably 1:0.14-0.86:0.86-0.14, wherein the molar equivalent of the diamine compound is 1, and the sum of the molar equivalents of the diacyl chloride compound and the dianhydride compound is 1. The molar ratio of the diamine compound to the diacyl chloride compound and the diamine compound may be 1:0.1:0.9, 1:0.14:0.86, 1:0.18:0.82, 1:0.2:0.8, 1:0.25:0.75, 1:0.3:0.7, 1:0.35:0.65, 1:0.4:0.6, 1:0.45:0.55, 1:0.5:0.5, 1:0.55:0.45, 1:0.6:0.4, 1:0.65:0.35, 1:0.7:0.3, 1:0.75:0.25, 1:0.8:0.2, 1:0.85:0.15, or 1:0.9:0.1, etc. Preferably, it is 1:0.14-0.86:0.86-0.14.

[0017] In the case of the above-mentioned molar ratio of the feed materials of the present invention, various characteristics of the polyamide-imide component can be effectively exhibited, and the optical properties and mechanical properties can be optimized.

[0018] In the present invention, the molar ratio of the diamine compound to the diacyl chloride compound is preferably 1:0.14-0.86. If the amount of the diacyl chloride compound added is greater than 0.14 relative to the molar number of the diamine compound, the mechanical physical properties of the polyimide film, such as tensile modulus and tensile strength, can be greatly improved. However, when the amount of the diacyl chloride compound added is too large (i.e., the molar number of the diacyl chloride compound added is greater than 0.86 relative to the diamine compound), further optical degradation such as the yellow index and light transmittance will occur.

[0019] Preferably, the weight average molecular weight of the polyamide-imide copolymer is 10,000-400,000, such as 10,000, 20,000, 30,000, 50,000, 80,000, 100,000, 120,000, 130,000, 150,000, 180,000, 200,000, 230,000, 250,000, 280,000, 300,000, 330,000, 350,000, 380,000 or 400,000, etc. In the present invention, when the weight average molecular weight of the copolymer resin is less than 10,000, the optical properties and mechanical properties of the polyamide-imide copolymer film may be deteriorated. However, when the weight average molecular weight is greater than 400,000, the resin will be difficult to form into a film due to excessive viscosity.

[0020] On the other hand, the present invention provides a method for preparing the polyamide-imide copolymer as described above, the preparation method comprising the following steps:

[0021] The polyamide-imide copolymer is obtained by polymerizing monomers including a dianhydride compound, a diamine compound and a diacid chloride compound.

[0022] Specifically, the preparation method comprises the following steps: reacting a diamine compound with a dianhydride compound to obtain a polymer having an imide precursor structure, then reacting the polymer with a diacyl chloride compound to obtain a copolymer having an imide precursor structure and an amide structure; finally, subjecting the imide precursor structure in the copolymer to a ring-closing reaction (imidization) to obtain a polyamide-imide resin.

[0023] The details are as follows:

[0024] (1) a dianhydride compound and a diamine compound are subjected to a polymerization reaction in a first solvent to obtain a polymer;

[0025] (2) subjecting the polymer obtained in step (1) to a polymerization reaction with a diacyl chloride compound to obtain a polyamic acid solution;

[0026] (3) adding an imidization catalyst and a dehydrating agent to the polyamic acid solution obtained in step (2) to imidize the polyamic acid solution, and precipitating the imidized polyamic acid solution in a second solvent to obtain a polyamide-imide copolymer.

[0027] In the present invention, first dianhydride compound and diamine compound are subjected to polyreaction in the first solvent, then the obtained polymer and diacyl chloride compound are subjected to polyreaction, polyamic acid solution is obtained, then imidization catalyst and dehydrating agent are added to imidize the polyamic acid solution, finally precipitate to obtain polyamide-imide copolymer resin solid, through the control of such reaction sequence, dianhydride monomer used in the present invention is first polymerized with diamine monomer to form larger diamine compound, finally polymerized with diacyl chloride to form copolymer resin. But it should be noted that the dianhydride monomer reaction rate used in the present invention is lower and is a reversible reaction when polymerized with diamine monomer. And diacyl chloride has greater reactivity, and after adding reaction, it will be polymerized into block unit structure with diamine monomer immediately, and the reaction is irreversible. Therefore, the block unit structure of this polymerization will be randomly embedded in the chain structure formed by dianhydride monomer and diamine monomer, forming an irregular embedded chain polymer structure.

[0028] Preferably, the first solvent in step (1) is not particularly limited, and can be selected from ketones such as γ-butyrolactone, 1,3-dimethyl-2-imidazolidinone, methyl ethyl ketone, cyclohexanone, cyclopentanone, 4-hydroxy-4-methyl-2-pentanone; aromatic hydrocarbons such as toluene, xylene, tetramethylbenzene; glycol ethers such as ethylene glycol monoethyl ether, ethylene glycol monomethyl ether, ethylene glycol monobutyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether, diethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, dipropylene glycol diethyl ether, triethylene glycol monoethyl ether; ethyl acetate, butyl acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, diethylene glycol mono One or at least two polar solvents selected from acetates such as ethyl ether acetate and dipropylene glycol monomethyl ether acetate; alcohols such as methanol, ethanol, propanol, ethylene glycol, propylene glycol, and carbitol; amides such as N,N-dimethylpropionamide (DMPA), N,N-diethylpropionamide (DEPA), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide (DEAc), N,N-dimethylformamide (DMF), N,N-diethylformamide (DEF), N-methylpyrrolidone (NMP), N-ethylpyrrolidone (NEP), and N,N-dimethylmethoxyacetamide are used as the first solvent.

[0029] The amount of solvent as mentioned above is not particularly limited. Yet, in order to obtain the polyamic acid solution with suitable molecular weight and viscosity, the gross weight of the polyamic acid solution is 100%, and the consumption of the first solvent can be 5~95wt%, for example 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 90wt% or 95wt%, preferably 20~90wt%.

[0030] Preferably, the polymerization reaction temperature in step (1) is 25°C to 50°C, for example, 25°C, 28°C, 30°C, 35°C, 40°C, 45°C, 48°C or 50°C, and the reaction time is 8 to 72 hours, for example, 8 hours, 10 hours, 12 hours, 15 hours, 18 hours, 20 hours, 22 hours or 72 hours.

[0031] Preferably, the polymerization reaction temperature in step (2) is 25°C to 50°C, for example, 25°C, 28°C, 30°C, 35°C, 40°C, 45°C, 48°C or 50°C, and the reaction time is 8 to 72 hours, for example, 8 hours, 10 hours, 12 hours, 15 hours, 18 hours, 20 hours, 22 hours or 72 hours.

[0032] The imidization method can be any method, and can be carried out by thermal imidization or by chemical imidization with a dehydrating agent and a catalyst, or a method combining thermal imidization and chemical imidization. In the imidization process, the heating conditions can be determined according to the type of the polyamic acid solution and the thickness of the film to be prepared.

[0033] The imidization catalyst in step (3) can be used alone or in combination, and any one of triethylamine, diisopropylethylamine, N-methylpiperidine, pyridine, 2-methylpyridine, 3-methylpyridine, 4-methylpyridine, 3-ethylpyridine, 3,5-dimethylpyridine, 3,5-diethylpyridine, isoquinoline, imidazole, 1-methylimidazole, 2-methylimidazole or 1,2-dimethylimidazole or a combination of at least two thereof can be used; preferably pyridine.

[0034] Preferably, the dehydrating agent in step (3) can be used alone or in combination with anhydrides such as acetic anhydride, propionic anhydride, trifluoroacetic anhydride, and phosphites such as triethyl phosphite, tributyl phosphite, dimethyl phosphate, diethyl phosphite, and triphenyl phosphite. Acetic anhydride is preferred.

[0035] In the present invention, a solvent that cannot dissolve the polyamic acid polymer can be used as the second solvent. In addition, the principle of solid precipitation can be utilized by using the solubility difference, and a solvent with a lower polarity than the first solvent can be used as the second solvent. Specifically, the second solvent can be selected from any one or a combination of at least two of water, alcohol, ether or ketone.

[0036] In the present invention, although there is no particular limitation on the amount of the second solvent, the preferred amount of the second solvent is 5 to 20 times the total weight of the polyamic acid solution to be prepared, for example 5 times, 6 times, 7 times, 8 times, 10 times, 12 times, 15 times, 18 times or 20 times.

[0037] Preferably, the precipitation in step (3) is followed by filtration and drying.

[0038] After filtering the obtained polyamide-imide copolymer resin solid, the filtered resin solid can be dried at a temperature of 50 to 150° C. (e.g., 50° C., 70° C., 80° C., 100° C., 110° C., 120° C., 130° C., 140° C., or 150° C.) for 2 to 72 hours (e.g., 2 hours, 5 hours, 8 hours, 10 hours, 12 hours, 15 hours, 18 hours, 20 hours, 22 hours, or 72 hours), considering the boiling points of the first solvent remaining in the second solvent and the solidified polyamide-imide copolymer resin.

[0039] In another aspect, the present invention provides a polyamide-imide copolymer film, wherein the polyamide-imide copolymer film is formed of the polyamide-imide copolymer as described above.

[0040] In the present invention, the polyamide-imide copolymer film is obtained by dissolving a polyamide-imide copolymer in a solvent to obtain a polyamide-imide copolymer solution, and then casting the solution on a support and then drying to obtain the polyamide-imide copolymer film.

[0041] In the present invention, the solvent is not particularly limited, and at least one polar solvent (known reaction solvent) selected from m-cresol, N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), dimethylacetamide (DMAc), dimethyl sulfoxide (DMSO), acetone and diethyl acetate can be used as the solvent. In addition, low boiling point solvents such as tetrahydrofuran (THF) and chloroform, or low absorption solvents such as γ-butyrolactone can also be used as the solvent.

[0042] In the present invention, there is no particular limitation on the support, and any support commonly used in the art may be used without restriction. Non-limiting examples of the support include glass, stainless steel, or plastic films such as polyethylene terephthalate, polyethylene naphthalate, polypropylene, polyethylene, cellulose triacetate, cellulose diacetate, poly(meth)acrylate alkyl esters, poly(meth)acrylate copolymers, polyvinyl chloride, polyvinyl alcohol, polytetrafluoroethylene, and polytrifluoroethylene.

[0043] In the present invention, for the drying process of the film, it can be slowly heated at a heating rate of 1 to 10°C / min (e.g., 1°C / min, 2°C / min, 4°C / min, 5°C / min, 7°C / min, 9°C / min or 10°C / min) within 40 to 400°C for 1 minute to 8 hours (e.g., 1 minute, 5 minutes, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 5 hours, 6 hours, 7 hours or 8 hours) to obtain a polyamide-imide copolymer film. In addition, the heat treatment can be carried out in a separate vacuum oven or an oven filled with an inert gas, etc., and is not necessarily limited thereto.

[0044] In the present invention, there is no particular limitation on the thickness of the polyamide-imide copolymer film. For example, the thickness of the polyamide-imide copolymer film may be 10 to 250 μm, such as 10 μm, 20 μm, 30 μm, 50 μm, 80 μm, 100 μm, 130 μm, 150 μm, 180 μm, 200 μm, 220 μm or 250 μm, preferably 25 to 150 μm.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] The polyamide-imide copolymer of the present invention can impart excellent mechanical properties to the film and has excellent optical properties. DETAILED DESCRIPTION

[0047] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0048] Example 1

[0049] Preparation of polyamide-imide copolymer

[0050] In a 1000 mL reactor, nitrogen was introduced into the reactor, 594.41 g of N, N-dimethylacetamide (DMAc) was added thereto, and then heated to 25°C. Then, 57.64 g (0.18 mol) of TFMB was dissolved in N, N-dimethylacetamide (DMAc) to obtain a first solution, and the first solution was maintained at 25°C. Subsequently, 16.5 g (0.036 mol) of BPAF, 3.53 g (0.018 mol) of CBDA and 5.30 g (0.018 mol) of S-BPDA were added to the first solution, respectively, and then stirred for 24 hours to dissolve and react to obtain a second solution, and the second solution was maintained at 25°C. Next, 20.10 g (0.099 mol) of TPC and 1.83 (0.009 mol) of IPC were added to the second solution to obtain a polyamic acid solution with a solid content of 15 wt%.

[0051] Next, 28.48 g of pyridine and 36.75 g of acetic anhydride were added to the polyamic acid solution, and after stirring at 25°C for 24 hours, the weight average molecular weight of the reaction solution measured by GPC was 367,000. Then, 20 L of deionized water was used for precipitation. Next, the precipitated solid was filtered and then vacuum dried at 50°C for 24 hours to obtain 99.66 g of polyamide-imide copolymer powder.

[0052] Preparation of polyamide-imide copolymer film

[0053] The above 99.66g polyamide-imide copolymer powder was dissolved in 564.75g of N,N-dimethylacetamide (DMAc) to obtain a solution with a concentration of 15wt%. The obtained solution was coated on a stainless steel substrate and cast to a thickness of 900um, then slowly heated from 50°C to 180°C in a hot vacuum oven according to a gradient for 200 minutes to form a film, and then slowly cooled. The film was peeled off from the stainless steel substrate and fixed to the frame by pins. Finally, the polyamide-imide copolymer film was heat treated at 280°C for 30 minutes.

[0054] Example 2

[0055] In a 1000 mL reactor, nitrogen was introduced into the reactor, 577.67 g of N, N-dimethylacetamide (DMAc) was added thereto, and then heated to 25°C. Then, 57.64 g (0.18 mol) of TFMB was dissolved in N, N-dimethylacetamide (DMAc) to obtain a first solution, and the first solution was maintained at 25°C. Subsequently, 8.25 g (0.018 mol) of BPAF, 3.53 g (0.018 mol) of CBDA and 10.59 g (0.036 mol) of S-BPDA were added to the first solution, respectively, and then stirred for 24 hours to dissolve and react to obtain a second solution, and the second solution was maintained at 25°C. Next, 20.10 g (0.099 mol) of TPC and 1.83 (0.009 mol) of IPC were added to the second solution to obtain a polyamic acid solution with a solid content of 15 wt%.

[0056] Next, 28.48 g of pyridine and 36.75 g of acetic anhydride were added to the polyamic acid solution, and after stirring at 25°C for 24 hours, the weight average molecular weight of the reaction solution measured by GPC was 346,000. Then, 20 L of deionized water was used for precipitation. Next, the precipitated solid was filtered and then vacuum dried at 50°C for 24 hours to obtain 98.19 g of polyamide-imide copolymer powder.

[0057] Preparation of polyamide-imide copolymer film

[0058] The above 98.19g polyamide-imide copolymer powder was dissolved in 556.40g N,N-dimethylacetamide (DMAc) to obtain a solution with a concentration of 15wt%. The obtained solution was coated on a stainless steel substrate and cast to a thickness of 900um, then slowly heated from 50°C to 180°C in a hot vacuum oven according to a gradient for 200 minutes to form a film, and then slowly cooled. The film was peeled off from the stainless steel substrate and fixed to the frame by pins. Finally, the polyamide-imide copolymer film was heat treated at 280°C for 30 minutes.

[0059] Example 3

[0060] In a 1000 mL reactor, nitrogen was introduced into the reactor, 603.72 g of N, N-dimethylacetamide (DMAc) was added thereto, and then heated to 25° C. Then, 57.64 g (0.18 mol) of TFMB was dissolved in N, N-dimethylacetamide (DMAc) to obtain a first solution, and the first solution was maintained at 25° C. Subsequently, 16.50 g (0.036 mol) of BPAF, 3.53 g (0.018 mol) of CBDA and 10.59 g (0.036 mol) of S-BPDA were added to the first solution, respectively, and then stirred for 24 hours to dissolve and react to obtain a second solution, and the second solution was maintained at 25° C. Next, 9.14 g (0.045 mol) of TPC and 9.14 (0.045 mol) of IPC were added to the second solution to obtain a polyamic acid solution with a solid content of 15 wt%.

[0061] Next, 35.60 g of pyridine and 45.94 g of acetic anhydride were added to the polyamic acid solution, and after stirring at 25°C for 24 hours, the weight average molecular weight of the reaction solution measured by GPC was 368,000. Then, 20 L of deionized water was used for precipitation. Next, the precipitated solid was filtered and then vacuum dried at 50°C for 24 hours to obtain 102.51 g of polyamide-imide copolymer powder.

[0062] Preparation of polyamide-imide copolymer film

[0063] The above 102.51g polyamide-imide copolymer powder was dissolved in 580.89g N,N-dimethylacetamide (DMAc) to obtain a solution with a concentration of 15wt%. The obtained solution was coated on a stainless steel substrate and cast to a thickness of 900um, then slowly heated from 50°C to 180°C in a hot vacuum oven according to a gradient for 200 minutes to form a film, and then slowly cooled. The film was peeled off from the stainless steel substrate and fixed to the frame by pins. Finally, the polyamide-imide copolymer film was heat treated at 280°C for 30 minutes.

[0064] Example 4

[0065] In a 1000 mL reactor, nitrogen was introduced into the reactor, 622.36 g of N, N-dimethylacetamide (DMAc) was added thereto, and then heated to 25° C. Then, 57.64 g (0.18 mol) of TFMB was dissolved in N, N-dimethylacetamide (DMAc) to obtain a first solution, and the first solution was maintained at 25° C. Subsequently, 21.45 g (0.0468 mol) of BPAF, 7.06 g (0.036 mol) of CBDA, and 12.71 g (0.0432 mol) of S-BPDA were added to the first solution, respectively, and then stirred for 24 hours to dissolve and react to obtain a second solution, and the second solution was maintained at 25° C. Next, 10.23 g (0.0504 mol) of TPC and 0.73 g (0.0036 mol) of IPC were added to the second solution to obtain a polyamic acid solution having a solid content of 15 wt %.

[0066] Next, 49.83 g of pyridine and 64.32 g of acetic anhydride were added to the polyamic acid solution, and after stirring at 25°C for 24 hours, the weight average molecular weight of the reaction solution measured by GPC was 346,000. Then, 20 L of deionized water was used for precipitation. Next, the precipitated solid was filtered and then vacuum dried at 50°C for 24 hours to obtain 105.09 g of polyamide-imide copolymer powder.

[0067] Preparation of polyamide-imide copolymer film

[0068] The above 105.09g polyamide-imide copolymer powder was dissolved in 595.48g N,N-dimethylacetamide (DMAc) to obtain a solution with a concentration of 15wt%. The obtained solution was coated on a stainless steel substrate and cast to a thickness of 900um, then slowly heated from 50°C to 180°C in a hot vacuum oven according to a gradient for 200 minutes to form a film, and then slowly cooled. The film was peeled off from the stainless steel substrate and fixed to the frame by pins. Finally, the polyamide-imide copolymer film was heat treated at 280°C for 30 minutes.

[0069] Example 5

[0070] In a 1000 mL reactor, nitrogen was introduced into the reactor, 559.06 g of N, N-dimethylacetamide (DMAc) was added thereto, and then heated to 25°C. Then, 57.64 g (0.18 mol) of TFMB was dissolved in N, N-dimethylacetamide (DMAc) to obtain a first solution, and the first solution was maintained at 25°C. Subsequently, 8.25 g (0.018 mol) of BPAF and 3.53 g (0.018 mol) of CBDA were added to the first solution, respectively, and then stirred for 24 hours to dissolve and react to obtain a second solution, and the second solution was maintained at 25°C. Next, 25.58 g (0.126 mol) of TPC and 3.65 (0.018 mol) of IPC were added to the second solution to obtain a polyamic acid solution with a solid content of 15 wt%.

[0071] Next, 14.24 g of pyridine and 18.38 g of acetic anhydride were added to the polyamic acid solution, and after stirring at 25°C for 24 hours, the weight average molecular weight of the reaction solution measured by GPC was 343,000. Then, 20 L of deionized water was used for precipitation. Next, the precipitated solid was filtered and then vacuum dried at 50°C for 24 hours to obtain 95.6 g of polyamide-imide copolymer powder.

[0072] Preparation of polyamide-imide copolymer film

[0073] The above 95.6g polyamide-imide copolymer powder was dissolved in 541.72g of N,N-dimethylacetamide (DMAc) to obtain a solution with a concentration of 15wt%. The obtained solution was coated on a stainless steel substrate and cast to a thickness of 900um, then slowly heated from 50°C to 180°C in a hot vacuum oven according to a gradient for 200 minutes to form a film, and then slowly cooled. The film was peeled off from the stainless steel substrate and fixed to the frame by pins. Finally, the polyamide-imide copolymer film was heat treated at 280°C for 30 minutes.

[0074] Example 6

[0075] In a 1000 mL reactor, nitrogen was introduced into the reactor, 569.07 g of N, N-dimethylacetamide (DMAc) was added thereto, and then heated to 25°C. Then, 57.64 g (0.18 mol) of TFMB was dissolved in N, N-dimethylacetamide (DMAc) to obtain a first solution, and the first solution was maintained at 25°C. Subsequently, 8.25 g (0.018 mol) of BPAF and 5.3 g (0.018 mol) of S-BPDA were added to the first solution, respectively, and then stirred for 24 hours to dissolve and react to obtain a second solution, and the second solution was maintained at 25°C. Next, 25.58 g (0.126 mol) of TPC and 3.65 (0.018 mol) of IPC were added to the second solution to obtain a polyamic acid solution with a solid content of 15 wt%.

[0076] Next, 14.24 g of pyridine and 18.38 g of acetic anhydride were added to the polyamic acid solution, and after stirring at 25°C for 24 hours, the weight average molecular weight of the reaction solution measured by GPC was 334,000. Then, 20 L of deionized water was used for precipitation. Next, the precipitated solid was filtered and then vacuum dried at 50°C for 24 hours to obtain 96.48 g of polyamide-imide copolymer powder.

[0077] Preparation of polyamide-imide copolymer film

[0078] The above 96.48g polyamide-imide copolymer powder was dissolved in 546.73g N,N-dimethylacetamide (DMAc) to obtain a solution with a concentration of 15wt%. The obtained solution was coated on a stainless steel substrate and cast to a thickness of 900um, then slowly heated from 50°C to 180°C in a hot vacuum oven according to a gradient for 200 minutes to form a film, and then slowly cooled. The film was peeled off from the stainless steel substrate and fixed to the frame by pins. Finally, the polyamide-imide copolymer film was heat treated at 280°C for 30 minutes.

[0079] Example 7

[0080] In a 1000 mL reactor, nitrogen was introduced into the reactor, 559.06 g of N, N-dimethylacetamide (DMAc) was added thereto, and then heated to 25° C. Then, 57.64 g (0.18 mol) of TFMB was dissolved in N, N-dimethylacetamide (DMAc) to obtain a first solution, and the first solution was maintained at 25° C. Subsequently, 8.25 g (0.018 mol) of BPAF and 3.53 g (0.018 mol) of CBDA were added to the first solution, respectively, and then stirred for 24 hours to dissolve and react to obtain a second solution, and the second solution was maintained at 25° C. Next, 29.23 g (0.144 mol) of TPC was added to the second solution to obtain a polyamic acid solution with a solid content of 15 wt%.

[0081] Next, 14.24 g of pyridine and 18.38 g of acetic anhydride were added to the polyamic acid solution, and after stirring at 25°C for 24 hours, the weight average molecular weight of the reaction solution measured by GPC was 363,000. Then, 20 L of deionized water was used for precipitation. Next, the precipitated solid was filtered and then vacuum dried at 50°C for 24 hours to obtain 93.98 g of polyamide-imide copolymer powder.

[0082] Preparation of polyamide-imide copolymer film

[0083] The above 93.98g polyamide-imide copolymer powder was dissolved in 532.54g of N,N-dimethylacetamide (DMAc) to obtain a solution with a concentration of 15wt%. The obtained solution was coated on a stainless steel substrate and cast to a thickness of 900um, then slowly heated from 50°C to 180°C in a hot vacuum oven according to a gradient for 200 minutes to form a film, and then slowly cooled. The film was peeled off from the stainless steel substrate and fixed to the frame by pins. Finally, the polyamide-imide copolymer film was heat treated at 280°C for 30 minutes.

[0084] Example 8

[0085] In a 1000 mL reactor, nitrogen was introduced into the reactor, 571.73 g of N, N-dimethylacetamide (DMAc) was added thereto, and then heated to 25° C. Then, 57.64 g (0.18 mol) of TFMB was dissolved in N, N-dimethylacetamide (DMAc) to obtain a first solution, and the first solution was maintained at 25° C. Subsequently, 12.38 g (0.027 mol) of BPAF and 5.29 g (0.027 mol) of CBDA were added to the first solution, respectively, and then stirred for 24 hours to dissolve and react to obtain a second solution, and the second solution was maintained at 25° C. Next, 25.58 g (0.126 mol) of TPC was added to the second solution to obtain a polyamic acid solution having a solid content of 15 wt%.

[0086] Next, 21.36 g of pyridine and 27.56 g of acetic anhydride were added to the polyamic acid solution, and after stirring at 25°C for 24 hours, the weight average molecular weight of the reaction solution measured by GPC was 343,000. Then, 20 L of deionized water was used for precipitation. Next, the precipitated solid was filtered and then vacuum dried at 50°C for 24 hours to obtain 96.61 g of polyamide-imide copolymer powder.

[0087] Preparation of polyamide-imide copolymer film

[0088] The above 96.61g polyamide-imide copolymer powder was dissolved in 547.47g N,N-dimethylacetamide (DMAc) to obtain a solution with a concentration of 15wt%. The obtained solution was coated on a stainless steel substrate and cast to a thickness of 900um, then slowly heated from 50°C to 180°C in a hot vacuum oven according to a gradient for 200 minutes to form a film, and then slowly cooled. The film was peeled off from the stainless steel substrate and fixed to the frame by pins. Finally, the polyamide-imide copolymer film was heat treated at 280°C for 30 minutes.

[0089] Example 9

[0090] In a 1000 mL reactor, nitrogen was introduced into the reactor, 586.74 g of N, N-dimethylacetamide (DMAc) was added thereto, and then heated to 25°C. Then, 57.64 g (0.18 mol) of TFMB was dissolved in N, N-dimethylacetamide (DMAc) to obtain a first solution, and the first solution was maintained at 25°C. Subsequently, 12.38 g (0.027 mol) of BPAF and 7.94 g (0.027 mol) of S-BPDA were added to the first solution, respectively, and then stirred for 24 hours to dissolve and react to obtain a second solution, and the second solution was maintained at 25°C. Next, 25.58 g (0.126 mol) of TPC was added to the second solution to obtain a polyamic acid solution with a solid content of 15 wt%.

[0091] Next, 21.36 g of pyridine and 27.56 g of acetic anhydride were added to the polyamic acid solution, and after stirring at 25°C for 24 hours, the weight average molecular weight of the reaction solution measured by GPC was 339,000. Then, 20 L of deionized water was used for precipitation. Next, the precipitated solid was filtered and then vacuum dried at 50°C for 24 hours to obtain 98.52 g of polyamide-imide copolymer powder.

[0092] Preparation of polyamide-imide copolymer film

[0093] The above 98.52g polyamide-imide copolymer powder was dissolved in 558.28g N,N-dimethylacetamide (DMAc) to obtain a solution with a concentration of 15wt%. The obtained solution was coated on a stainless steel substrate and cast to a thickness of 900um, then slowly heated from 50°C to 180°C in a hot vacuum oven according to a gradient for 200 minutes to form a film, and then slowly cooled. The film was peeled off from the stainless steel substrate and fixed to the frame by pins. Finally, the polyamide-imide copolymer film was heat treated at 280°C for 30 minutes.

[0094] Example 10

[0095] In a 1000 mL reactor, nitrogen was introduced into the reactor, 584.41 g of N, N-dimethylacetamide (DMAc) was added thereto, and then heated to 25° C. Then, 57.64 g (0.18 mol) of TFMB was dissolved in N, N-dimethylacetamide (DMAc) to obtain a first solution, and the first solution was maintained at 25° C. Subsequently, 16.50 g (0.036 mol) of BPAF and 7.06 g (0.036 mol) of CBDA were added to the first solution, respectively, and then stirred for 24 hours to dissolve and react to obtain a second solution, and the second solution was maintained at 25° C. Next, 21.93 g (0.108 mol) of TPC was added to the second solution to obtain a polyamic acid solution with a solid content of 15 wt%.

[0096] Next, 28.48 g of pyridine and 36.75 g of acetic anhydride were added to the polyamic acid solution, and after stirring at 25°C for 24 hours, the weight average molecular weight of the reaction solution measured by GPC was 374,000. Then, 20 L of deionized water was used for precipitation. Next, the precipitated solid was filtered and then vacuum dried at 50°C for 24 hours to obtain 98.81 g of polyamide-imide copolymer powder.

[0097] Preparation of polyamide-imide copolymer film

[0098] The above 98.81g polyamide-imide copolymer powder was dissolved in 559.91g N,N-dimethylacetamide (DMAc) to obtain a solution with a concentration of 15wt%. The obtained solution was coated on a stainless steel substrate and cast to a thickness of 900um, then slowly heated from 50°C to 180°C in a hot vacuum oven according to a gradient for 200 minutes to form a film, and then slowly cooled. The film was peeled off from the stainless steel substrate and fixed to the frame by pins. Finally, the polyamide-imide copolymer film was heat treated at 280°C for 30 minutes.

[0099] Embodiment 11

[0100] In a 1000 mL reactor, nitrogen was introduced into the reactor, 541.61 g of N, N-dimethylacetamide (DMAc) was added thereto, and then heated to 25° C. Then, 57.64 g (0.18 mol) of TFMB was dissolved in N, N-dimethylacetamide (DMAc) to obtain a first solution, and the first solution was maintained at 25° C. Subsequently, 7.06 g (0.036 mol) of CBDA and 5.3 g (0.018 mol) of S-BPDA were added to the first solution, respectively, and then stirred for 24 hours to dissolve and react to obtain a second solution, and the second solution was maintained at 25° C. Next, 12.79 (0.063 mol) of TPC and 12.79 (0.063 mol) of IPC were added to the second solution to obtain a polyamic acid solution with a solid content of 15 wt%.

[0101] Next, 21.36 g of pyridine and 27.56 g of acetic anhydride were added to the polyamic acid solution, and after stirring at 25°C for 24 hours, the weight average molecular weight of the reaction solution measured by GPC was 336,000. Then, 20 L of deionized water was used for precipitation. Next, the precipitated solid was filtered and then vacuum dried at 50°C for 24 hours to obtain 92.46 g of polyamide-imide copolymer powder.

[0102] Preparation of polyamide-imide copolymer film

[0103] The above 92.46g polyamide-imide copolymer powder was dissolved in 523.49g N,N-dimethylacetamide (DMAc) to obtain a solution with a concentration of 15wt%. The obtained solution was coated on a stainless steel substrate and cast to a thickness of 900um, then slowly heated from 50°C to 180°C in a hot vacuum oven according to a gradient for 200 minutes to form a film, and then slowly cooled. The film was peeled off from the stainless steel substrate and fixed to the frame by pins. Finally, the polyamide-imide copolymer film was heat treated at 280°C for 30 minutes.

[0104] Example 12

[0105] In a 1000 mL reactor, nitrogen was introduced into the reactor, 570.92 g of N, N-dimethylacetamide (DMAc) was added thereto, and then heated to 25° C. Then, 57.64 g (0.18 mol) of TFMB was dissolved in N, N-dimethylacetamide (DMAc) to obtain a first solution, and the first solution was maintained at 25° C. Subsequently, 21.18 g (0.072 mol) of S-BPDA was added to the first solution, and then stirred for 24 hours to dissolve and react to obtain a second solution, and the second solution was maintained at 25° C. Next, 14.62 (0.072 mol) of TPC and 7.31 (0.036 mol) of IPC were added to the second solution to obtain a polyamic acid solution with a solid content of 15 wt%.

[0106] Next, 28.48 g of pyridine and 36.75 g of acetic anhydride were added to the polyamic acid solution, and after stirring at 25°C for 24 hours, the weight average molecular weight of the reaction solution measured by GPC was 364,000. Then, 20 L of deionized water was used for precipitation. Next, the precipitated solid was filtered and then vacuum dried at 50°C for 24 hours to obtain 96.96 g of polyamide-imide copolymer powder.

[0107] Preparation of polyamide-imide copolymer film

[0108] The above 96.96g polyamide-imide copolymer powder was dissolved in 549.45g of N,N-dimethylacetamide (DMAc) to obtain a solution with a concentration of 15wt%. The obtained solution was coated on a stainless steel substrate and cast to a thickness of 900um, then slowly heated from 50°C to 180°C in a hot vacuum oven according to a gradient for 200 minutes to form a film, and then slowly cooled. The film was peeled off from the stainless steel substrate and fixed to the frame by pins. Finally, the polyamide-imide copolymer film was heat treated at 280°C for 30 minutes.

[0109] Example 13

[0110] In a 1000 mL reactor, nitrogen was introduced into the reactor, 532.31 g of N, N-dimethylacetamide (DMAc) was added thereto, and then heated to 25° C. Then, 57.64 g (0.18 mol) of TFMB was dissolved in N, N-dimethylacetamide (DMAc) to obtain a first solution, and the first solution was maintained at 25° C. Subsequently, 7.06 g (0.036 mol) of CBDA was added to the first solution, and then stirred for 24 hours to dissolve and react to obtain a second solution, and the second solution was maintained at 25° C. Next, 21.93 (0.108 mol) of TPC and 7.31 (0.036 mol) of IPC were added to the second solution to obtain a polyamic acid solution with a solid content of 15 wt%.

[0111] Next, 14.24 g of pyridine and 18.38 g of acetic anhydride were added to the polyamic acid solution, and after stirring at 25°C for 24 hours, the weight average molecular weight of the reaction solution measured by GPC was 341,000. Then, 20 L of deionized water was used for precipitation. Next, the precipitated solid was filtered and then vacuum dried at 50°C for 24 hours to obtain 90.03 g of polyamide-imide copolymer powder.

[0112] Preparation of polyamide-imide copolymer film

[0113] The above 90.03g polyamide-imide copolymer powder was dissolved in 510.15g N,N-dimethylacetamide (DMAc) to obtain a solution with a concentration of 15wt%. The obtained solution was coated on a stainless steel substrate and cast to a thickness of 900um, then slowly heated from 50°C to 180°C in a hot vacuum oven according to a gradient for 200 minutes to form a film, and then slowly cooled. The film was peeled off from the stainless steel substrate and fixed to the frame by pins. Finally, the polyamide-imide copolymer film was heat treated at 280°C for 30 minutes.

[0114] Embodiment 14

[0115] In a 1000 mL reactor, nitrogen was introduced into the reactor, 532.73 g of N, N-dimethylacetamide (DMAc) was added thereto, and then heated to 25° C. Then, 57.64 g (0.18 mol) of TFMB was dissolved in N, N-dimethylacetamide (DMAc) to obtain a first solution, and the first solution was maintained at 25° C. Subsequently, 4.94 g (0.0252 mol) of CBDA was added to the first solution, and then stirred for 24 hours to dissolve and react to obtain a second solution, and the second solution was maintained at 25° C. Next, 21.20 (0.1044 mol) of TPC and 10.23 (0.0504 mol) of IPC were added to the second solution to obtain a polyamic acid solution with a solid content of 15 wt%.

[0116] Next, 9.97 g of pyridine and 12.86 g of acetic anhydride were added to the polyamic acid solution, and after stirring at 25°C for 24 hours, the weight average molecular weight of the reaction solution measured by GPC was 345,000. Then, 20 L of deionized water was used for precipitation. Next, the precipitated solid was filtered and then vacuum dried at 50°C for 24 hours to obtain 89.91 g of polyamide-imide copolymer powder.

[0117] Preparation of polyamide-imide copolymer film

[0118] The above 89.91g polyamide-imide copolymer powder was dissolved in 509.49g N,N-dimethylacetamide (DMAc) to obtain a solution with a concentration of 15wt%. The obtained solution was coated on a stainless steel substrate and cast to a thickness of 900um, then slowly heated from 50°C to 180°C in a hot vacuum oven according to a gradient for 200 minutes to form a film, and then slowly cooled. The film was peeled off from the stainless steel substrate and fixed to the frame by pins. Finally, the polyamide-imide copolymer film was heat treated at 280°C for 30 minutes.

[0119] Embodiment 15

[0120] In a 1000 mL reactor, nitrogen was introduced into the reactor, 546.74 g of N, N-dimethylacetamide (DMAc) was added thereto, and then heated to 25° C. Then, 57.64 g (0.18 mol) of TFMB was dissolved in N, N-dimethylacetamide (DMAc) to obtain a first solution, and the first solution was maintained at 25° C. Subsequently, 7.41 g (0.0252 mol) of S-BPDA was added to the first solution, and then stirred for 24 hours to dissolve and react to obtain a second solution, and the second solution was maintained at 25° C. Next, 21.20 (0.1044 mol) of TPC and 10.23 (0.0504 mol) of IPC were added to the second solution to obtain a polyamic acid solution with a solid content of 15 wt%.

[0121] Next, 9.97 g of pyridine and 12.86 g of acetic anhydride were added to the polyamic acid solution, and after stirring at 25°C for 24 hours, the weight average molecular weight of the reaction solution measured by GPC was 371,000. Then, 20 L of deionized water was used for precipitation. Next, the precipitated solid was filtered and then vacuum dried at 50°C for 24 hours to obtain 92.95 g of polyamide-imide copolymer powder.

[0122] Preparation of polyamide-imide copolymer film

[0123] The above 92.95g polyamide-imide copolymer powder was dissolved in 526.72g of N,N-dimethylacetamide (DMAc) to obtain a solution with a concentration of 15wt%. The obtained solution was coated on a stainless steel substrate and cast to a thickness of 900um, then slowly heated from 50°C to 180°C in a hot vacuum oven according to a gradient for 200 minutes to form a film, and then slowly cooled. The film was peeled off from the stainless steel substrate and fixed to the frame by pins. Finally, the polyamide-imide copolymer film was heat treated at 280°C for 30 minutes.

[0124] Comparative Example 1

[0125] In a 1000 mL reactor, nitrogen was introduced into the reactor, 584.58 g of N, N-dimethylacetamide (DMAc) was added thereto, and then heated to 25° C. Then, 57.64 g (0.18 mol) of TFMB was dissolved in N, N-dimethylacetamide (DMAc) to obtain a first solution, and the first solution was maintained at 25° C. Subsequently, 11.99 g (0.027 mol) of 6FDA (4, 4'-(hexafluoroisopropylene) diphthalic anhydride) and 7.94 g (0.027 mol) of S-BPDA were added to the first solution, respectively, and then stirred for 24 hours to dissolve and react to obtain a second solution, and the second solution was maintained at 25° C. Next, 25.58 g (0.126 mol) of TPC was added to the second solution to obtain a polyamic acid solution with a solid content of 15 wt%.

[0126] Next, 21.36 g of pyridine and 27.56 g of acetic anhydride were added to the polyamic acid solution, stirred at 25° C. for 24 h, and then precipitated with 20 L of deionized water. Next, the precipitated solid was filtered and then vacuum dried at 50° C. for 24 h to obtain 98.7 g of polyamide-imide copolymer powder.

[0127] Preparation of polyamide-imide copolymer film

[0128] The above 98.7g polyamide-imide copolymer powder was dissolved in 559.33g of N,N-dimethylacetamide (DMAc) to obtain a solution with a concentration of 15wt%. The obtained solution was coated on a stainless steel substrate and cast to a thickness of 900um, then slowly heated from 50°C to 180°C in a hot vacuum oven according to a gradient for 200 minutes to form a film, and then slowly cooled. The film was peeled off from the stainless steel substrate and fixed to the frame by pins. Finally, the polyamide-imide copolymer film was heat treated at 280°C for 30 minutes.

[0129] Comparative Example 2

[0130] In a 1000 mL reactor, nitrogen was introduced into the reactor, 581.51 g of N, N-dimethylacetamide (DMAc) was added thereto, and then heated to 25° C. Then, 57.64 g (0.18 mol) of TFMB was dissolved in N, N-dimethylacetamide (DMAc) to obtain a first solution, and the first solution was maintained at 25° C. Subsequently, 15.99 g (0.036 mol) of 6FDA and 7.06 g (0.036 mol) of CBDA were added to the first solution, respectively, and then stirred for 24 hours to dissolve and react to obtain a second solution, and the second solution was maintained at 25° C. Next, 21.93 g (0.108 mol) of TPC was added to the second solution to obtain a polyamic acid solution with a solid content of 15 wt%.

[0131] Next, 28.48 g of pyridine and 36.75 g of acetic anhydride were added to the polyamic acid solution, stirred at 25° C. for 24 h, and then precipitated with 20 L of deionized water. Next, the precipitated solid was filtered and then vacuum dried at 50° C. for 24 h to obtain 99.44 g of polyamide-imide copolymer powder.

[0132] Preparation of polyamide-imide copolymer film

[0133] The above 99.44g polyamide-imide copolymer powder was dissolved in 563.47g N,N-dimethylacetamide (DMAc) to obtain a solution with a concentration of 15wt%. The obtained solution was coated on a stainless steel substrate and cast to a thickness of 900um, then slowly heated from 50°C to 180°C in a hot vacuum oven according to a gradient for 200 minutes to form a film, and then slowly cooled. The film was peeled off from the stainless steel substrate and fixed to the frame by pins. Finally, the polyamide-imide copolymer film was heat treated at 280°C for 30 minutes.

[0134] Comparative Example 3

[0135] In a 1000 mL reactor, nitrogen was introduced into the reactor, 533.01 g of N, N-dimethylacetamide (DMAc) was added thereto, and then heated to 25° C. Then, 57.64 g (0.18 mol) of TFMB was dissolved in N, N-dimethylacetamide (DMAc) to obtain a first solution, and the first solution was maintained at 25° C. Subsequently, 3.53 g (0.018 mol) of CBDA was added to the first solution, and then stirred for 24 hours to dissolve and react to obtain a second solution, and the second solution was maintained at 25° C. Next, 31.06 g (0.153 mol) of TPC and 1.83 (0.009 mol) of IPC were added to the second solution to obtain a polyamic acid solution with a solid content of 15 wt%.

[0136] Next, 7.12 g of pyridine and 9.19 g of acetic anhydride were added to the polyamic acid solution, stirred at 25° C. for 24 h, and then precipitated with 20 L of deionized water. Next, the precipitated solid was filtered and then vacuum dried at 50° C. for 24 h to obtain 89.6 g of polyamide-imide copolymer powder.

[0137] Preparation of polyamide-imide copolymer film

[0138] The above 89.6g polyamide-imide copolymer powder was dissolved in 507.73g of N,N-dimethylacetamide (DMAc) to obtain a solution with a concentration of 15wt%. The obtained solution was coated on a stainless steel substrate and cast to a thickness of 900um, then slowly heated from 50°C to 180°C in a hot vacuum oven according to a gradient for 200 minutes to form a film, and then slowly cooled. The film was peeled off from the stainless steel substrate and fixed to the frame by pins. Finally, the polyamide-imide copolymer film was heat treated at 280°C for 30 minutes.

[0139] Comparative Example 4

[0140] In a 1000 mL reactor, nitrogen was introduced into the reactor, 564.13 g of N, N-dimethylacetamide (DMAc) was added thereto, and then heated to 25° C. Then, 57.64 g (0.18 mol) of TFMB was dissolved in N, N-dimethylacetamide (DMAc) to obtain a first solution, and the first solution was maintained at 25° C. Subsequently, 8.25 g (0.018 mol) of BPAF, 24.71 g (0.126 mol) of CBDA and 5.3 g (0.018 mol) of S-BPDA were added to the first solution, respectively, and then stirred for 24 hours to dissolve and react to obtain a second solution, and the second solution was maintained at 25° C. Next, 3.65 g (0.018 mol) of TPC was added to the second solution to obtain a polyamic acid solution with a solid content of 15 wt%.

[0141] Next, 64.07 g of pyridine and 82.69 g of acetic anhydride were added to the polyamic acid solution, stirred at 25° C. for 24 h, and then precipitated with 20 L of deionized water. Next, the precipitated solid was filtered and then vacuum dried at 50° C. for 24 h to obtain 95.33 g of polyamide-imide copolymer powder.

[0142] Preparation of polyamide-imide copolymer film

[0143] The above 95.33g polyamide-imide copolymer powder was dissolved in 540.19g N,N-dimethylacetamide (DMAc) to obtain a solution with a concentration of 15wt%. The obtained solution was coated on a stainless steel substrate and cast to a thickness of 900um, then slowly heated from 50°C to 180°C in a hot vacuum oven according to a gradient for 200 minutes to form a film, and then slowly cooled. The film was peeled off from the stainless steel substrate and fixed to the frame by pins. Finally, the polyamide-imide copolymer film was heat treated at 280°C for 30 minutes.

[0144] Comparative Example 5

[0145] In a 1000 mL reactor, nitrogen was introduced into the reactor, 543.02 g of N, N-dimethylacetamide (DMAc) was added thereto, and then heated to 25° C. Then, 57.64 g (0.18 mol) of TFMB was dissolved in N, N-dimethylacetamide (DMAc) to obtain a first solution, and the first solution was maintained at 25° C. Subsequently, 5.3 g (0.018 mol) of S-BPDA was added to the first solution, and then stirred for 24 hours to dissolve and react to obtain a second solution, and the second solution was maintained at 25° C. Next, 31.06 g (0.153 mol) of TPC and 1.83 g (0.009 mol) of IPC were added to the second solution to obtain a polyamic acid solution with a solid content of 15 wt%.

[0146] Next, 7.12 g of pyridine and 9.19 g of acetic anhydride were added to the polyamic acid solution, stirred at 25° C. for 24 h, and then precipitated with 20 L of deionized water. Next, the precipitated solid was filtered and then vacuum dried at 50° C. for 24 h to obtain 91.38 g of polyamide-imide copolymer powder.

[0147] Preparation of polyamide-imide copolymer film

[0148] The above 91.38g polyamide-imide copolymer powder was dissolved in 517.80g N,N-dimethylacetamide (DMAc) to obtain a solution with a concentration of 15wt%. The obtained solution was coated on a stainless steel substrate and cast to a thickness of 900um, then slowly heated from 50°C to 180°C in a hot vacuum oven according to a gradient for 200 minutes to form a film, and then slowly cooled. The film was peeled off from the stainless steel substrate and fixed to the frame by pins. Finally, the polyamide-imide copolymer film was heat treated at 280°C for 30 minutes.

[0149] The properties of the polyamide-imide copolymer films prepared in the examples and comparative examples were tested, and the testing method was as follows:

[0150] (1) Yellowness Index (YI)

[0151] According to GB / T 39822-2021, the yellowness index of each film prepared in the examples and comparative examples was measured at 380-780 nm using SE7700 produced by Nippon Denshoku.

[0152] (2)Film thickness

[0153] The thickness of each of the prepared films was measured using PG-20A manufactured by TECLOCK.

[0154] (3) Tensile modulus, tensile strength and elongation at break

[0155] According to GB / T 1040.3-2006, the measurement is performed using UTM3365 produced by Instron. The thickness of the film is measured and the value is input into the instrument. The unit of modulus is GPa, the unit of tensile strength is MPa, and the unit of elongation at break is %.

[0156] (4) Light transmittance

[0157] According to the national standard GB / T 2410-2008, the total light transmittance (%) was measured in the entire region of 400-700 nm wavelength using COH-5500 produced by Nippon Denshoku.

[0158] (5) Weight average molecular weight

[0159] The weight average molecular weight of the polymer based on polystyrene conversion was measured using gel permeation chromatography (GPC, Waters Alliance, model: e2695).

[0160] The dosage of each substance in the embodiments and comparative examples is shown in Table 1, and the performance test results are shown in Table 2.

[0161] Table 1

[0162]

[0163]

[0164] Table 2

[0165] Thickness(μm) Modulus(GPa) YI Light transmittance (%) Example 1 50 7.3 1.90 86.5 Example 2 50 6.95 2.45 86.7 Example 3 50 6.15 2.50 84.5 Example 4 50 6.80 2.58 85.4 Example 5 50 5.45 1.75 83.4 Example 6 50 5.85 1.95 84.5 Example 7 50 5.65 2.00 80.7 Example 8 50 6.60 1.95 83.9 Example 9 50 7.25 1.90 89 Example 10 50 6.35 1.55 87.8 Embodiment 11 50 5.75 2.55 84.7 Example 12 50 6.45 2.35 82.6 Embodiment 13 50 5.15 2.45 85.5 Embodiment 14 50 7.10 1.60 83.4 Embodiment 15 50 7.15 1.68 84.6 Comparative Example 1 50 4.8 2.20 83 Comparative Example 2 50 4.4 2.75 84 Comparative Example 3 50 4.15 2.30 82.4 Comparative Example 4 50 gel - - Comparative Example 5 50 4.3 2.70 82

[0166] From the data in Table 1 and Table 2, the type and proportion of monomers directly affect the chemical structure and physical properties of the film. The combination of cyclic aliphatic tetracarboxylic dianhydride CBDA and fluorinated aromatic diamine TFMB will produce a synergistic effect, which can effectively reduce the charge transfer phenomenon between molecules and improve the optical transparency and stability of the material. The introduction of fluorenyl aromatic dianhydride BPAF can increase the band gap difference of molecular orbital energy levels, further enhancing the mechanical and optical properties of the material. The high-density distribution of rigid groups in the S-BPDA molecule enhances the interaction force between molecular chains, thereby improving the overall rigidity of the material. The TPC molecular structure gives it extremely high rigidity characteristics. When its proportion in the material increases, the interaction force between molecular chains is significantly enhanced, which greatly increases the modulus of the material. In order to avoid excessive sacrifice of material toughness, a suitable amount of flexible monomer IPC is introduced. The addition of flexible monomers effectively alleviates the brittleness problem caused by enhanced rigidity by increasing the flexibility of the molecular chain.

[0167] Referring to Table 2, it can be seen that the films prepared by the reaction of the proportions and monomer raw material combinations in Examples 1-10 can achieve higher modulus and higher transmittance. Compared with the use of 6FDA as a dianhydride for reaction film formation, the film formed by the ratio and raw material combination of the present invention has higher optical physical properties and mechanical physical properties. In addition, according to Comparative Example 4, the increase in the proportion of CBDA will cause the solution viscosity to become uncontrollably high or precipitation to occur, so the polymerization and preparation of the polyimide film cannot be carried out. According to Comparative Examples 3 and 5, it can be concluded that if the amount of TPC added is too high, the film will become brittle, causing the modulus and optical properties of the formed film to drop significantly.

[0168] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the polyamide-imide copolymer and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A polyamide-imide copolymer, characterized in that: The polyamide-imide copolymer is a copolymer obtained by polymerizing monomers, and the polymerizing monomers include dianhydride compounds, diamine compounds and diacid chloride compounds.

2. The polyamide-imide copolymer according to claim 1, characterized in that: The dianhydride compound is selected from any one or a combination of at least two of aliphatic or aromatic dianhydrides; Preferably, the dianhydride compound is selected from 1,2,4,5-cyclohexanetetracarboxylic dianhydride, 2,3',3,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride, 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, 1,2,3,4-cyclohexanetetracarboxylic dianhydride, 5-(2 Any one or a combination of at least two of 1,2-dicarboxylic acid dianhydride, 1,3-diethylcyclobutane-1,2,3,4-tetracarboxylic acid dianhydride, 1,3-diphenylcyclobutane-1,2,3,4-tetracarboxylic acid dianhydride, 4-(2,5-dioxytetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic acid dianhydride and their derivatives; More preferably, the dianhydride compound is selected from any one or more combinations of 3,3',4,4'-biphenyltetracarboxylic dianhydride, cyclobutanetetracarboxylic dianhydride and 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride.

3. The polyamide-imide copolymer according to claim 1 or 2, characterized in that: The diamine compound is selected from any one or a combination of at least two of 2,2'-bis(trifluoromethyl)benzidine, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis(3-amino-4-hydroxyphenyl)-hexafluoropropane, 3,4'-diaminodiphenyl ether, p-phenylenediamine, m-phenylenediamine, p-diaminodiphenylmethane, m-dianiline, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, bis(4-aminophenyl)sulfone, bis(3-aminophenyl)sulfone, 2,2-bis[4-(4-aminophenoxy)phenyl]propane and derivatives thereof; Further preferably, the diamine compound is 2,2'-bis(trifluoromethyl)benzidine; Preferably, the diacyl chloride compound is selected from any one or a combination of at least two of terephthaloyl chloride, isophthaloyl chloride, phthaloyl chloride, [1,1'-biphenyl]-4,4'-dicarboxylic acid chloride, 1,4-naphthalene dicarboxylic acid chloride, 2,6-naphthalene dicarboxylic acid chloride, 1,5-naphthalene dicarboxylic acid chloride, glutaryl chloride, adipoyl chloride and their derivatives; Preferably, the diacid chloride is any one of terephthaloyl chloride and isophthaloyl chloride or a combination of both.

4. The polyamide-imide copolymer according to any one of claims 1 to 3, characterized in that The molar ratio of the diamine compound to the diacyl chloride compound and the dianhydride compound is 1:0.1-0.9:0.9-0.1, preferably 1:0.14-0.86:0.86-0.14, wherein the molar equivalent of the diamine compound is 1, and the sum of the molar equivalents of the diacyl chloride compound and the dianhydride compound is 1.

5. The polyamide-imide copolymer according to any one of claims 1 to 4, characterized in that: The weight average molecular weight of the polyamide-imide copolymer is 10,000-400,000.

6. The method for preparing a polyamide-imide copolymer according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: The polyamide-imide copolymer is obtained by polymerizing monomers including a dianhydride compound, a diamine compound and a diacid chloride compound.

7. The preparation method according to claim 6, characterized in that: The preparation method comprises the following steps: (1) a dianhydride compound and a diamine compound are subjected to a polymerization reaction in a first solvent to obtain a polymer; (2) subjecting the polymer obtained in step (1) to a polymerization reaction with a diacyl chloride compound to obtain a polyamic acid solution; (3) adding an imidization catalyst and a dehydrating agent to the polyamic acid solution obtained in step (2) to imidize the polyamic acid solution, and precipitating the imidized polyamic acid solution in a second solvent to obtain a polyamide-imide copolymer.

8. The preparation method according to claim 7, characterized in that: Step (1) the first solvent is selected from any one or a combination of at least two of m-cresol, N-methyl-2-pyrrolidone, dimethylformamide, dimethylacetamide, dimethyl sulfoxide, acetone, diethyl acetate, tetrahydrofuran, chloroform or γ-butyrolactone; Preferably, based on the total weight of the polyamic acid solution, the amount of the first solvent is 15 to 95 wt %, preferably 20 to 90 wt %.

9. The preparation method according to claim 7 or 8, characterized in that: The polymerization reaction temperature in step (1) is 25° C. to 50° C., and the reaction time is 8 to 72 hours; Preferably, the polymerization reaction temperature in step (2) is 25°C to 50°C, and the reaction time is 8 to 72 hours; Preferably, the imidization catalyst in step (3) is pyridine; Preferably, the dehydrating agent in step (3) is acetic anhydride; Preferably, in step (3), the second solvent is selected from any one of water, alcohol, ether or ketone, or a combination of at least two thereof; Preferably, the amount of the second solvent is 5 to 20 times the total weight of the polyamic acid solution to be prepared; Preferably, the precipitation in step (3) is followed by filtration and drying; Preferably, the drying is carried out at a temperature of 50 to 150° C. for 2 to 72 hours.

10. A polyamide-imide copolymer film, characterized in that: The polyamide-imide copolymer film is formed by the polyamide-imide copolymer according to any one of claims 1 to 5; Preferably, the polyamide-imide copolymer film is obtained by dissolving a polyamide-imide copolymer in a solvent to obtain a polyamide-imide copolymer solution, and then casting the solution on a support and then drying to obtain the polyamide-imide copolymer film; Preferably, the solvent is selected from any one or a combination of at least two of m-cresol, N-methyl-2-pyrrolidone, dimethylformamide, dimethylacetamide, dimethyl sulfoxide, acetone, diethyl acetate, tetrahydrofuran, chloroform or γ-butyrolactone; Preferably, the drying operation is to slowly heat at a heating rate of 1 to 10°C / min at 40 to 400°C for 1 minute to 8 hours to obtain a polyamide-imide copolymer film; Preferably, the polyamide-imide copolymer film has a thickness of 10 to 250 μm, preferably 25 to 150 μm.